Different Perivascular Space Burdens in Idiopathic Rapid Eye Movement Sleep Behavior Disorder and Parkinson’s Disease - Si, Xiao-li; Gu, Lu-yan; Song, Zhe; Zhou, Cheng; Fang, Yi; Jin, Chong-yao; Wu, Jing-jing; Gao, Ting; Guo, Tao; Guan, Xiao-jun; Xu, Xiao-jun; Yin, Xin-zhen; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Excessive aggregation of α-synuclein is the key pathophysiological feature of Parkinson’s disease (PD). Rapid eye movement sleep behavior disorder (RBD) is also associated with synucleinopathies and considered as a powerful predictor of PD. Growing evidence suggests the diminished clearance of α-synuclein may be partly attributable to poor interstitial fluid drainage, which can be reflected by magnetic resonance imaging (MRI)-visible enlarged perivascular space (EPVS). However, the effect of MRI-visible EPVS on iRBD and PD, and their correlation with clinical characteristics remain unclear. Objective: To evaluate the clinical and neuroimaging significance of MRI-visible EPVS in iRBD and PD patients. Methods: We enrolled 33 iRBD patients, 82 PD (with and witout RBD) patients, and 35 healthy controls (HCs), who underwent clinical evaluation and 3.0 Tesla MRI. Two neurologists assessed MRI-visible EPVS in centrum semiovale (CSO), basal ganglia (BG), substantia nigra (SN), and brainstem (BS). Independent risk factors for iRBD and PD were investigated using multivariable logistic regression analysis. Spearman analysis was used to test the correlation of MRI-visible EPVS with clinical characteristics of patients. Results: iRBD patients had significantly higher EPVS burdens (CSO, BG, SN, and BS) than PD patients. Higher CSO-EPVS and BS-EPVS burdens were independent risk factors for iRBD. Furthermore, higher CSO-EPVS and SN-EPVS burdens were positively correlated with the severity of clinical symptom in iRBD patients, and higher BG-EPVS burden was positively correlated with the severity of cognitive impairment in PD patients. Conclusions: iRBD and PD patients have different MRI-visible EPVS burdens, which may be related with a compensatory mechanism in glymphatic system. Lower MRI-visible EPVS burden in PD patients may be a manifestation of severe brain waste drainage dysfunction. These findings shed light on the pathophysiologic relationship between iRBD and PD with respect to neuroimaging marker of PD.